Grant Richards collection of A.E. Housman material - Richards, Grant, 1872-1948.; Richards, Grant, 1872-1948.
Correspondence, manuscripts, typescripts, galley and page proofs, newspaper clippings, printed matter, musical scores, and other papers pertaining primarily to Richards's biography of A.E. Housman titled Housman, 1897-1936 (1941). Correspondents include A.E. Housman's brother and sister, Laurence Housman and Katharine E. Symons, Witter Bynner, John Carter, John Drinkwater, Ronald Firbank, B.W. Huebsch, Harold Nicolson, Maxwell E. Perkins, William Rothenstein, George Macaulay Trevelyan, Edmund Wilson, and Oxford University Press.
British author and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bynner, Witter, -- 1881-1968 -- Correspondence; Carter, John, -- 1905-1975 -- Correspondence; Drinkwater, John, -- 1882-1937 -- Correspondence; Firbank, Ronald, -- 1886-1926 -- Correspondence; Housman, A. E. -- 1859-1936 -- Correspondence; Housman, Laurence, -- 1865-1959 -- Correspondence; Huebsch, B. W. -- 1876-1964 -- Correspondence; Nicolson, Harold, -- 1886-1968 -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Rothenstein, William, -- 1872-1945 -- Correspondence; Symons, Katharine E. -- Correspondence; Trevelyan, George Macaulay, -- 1876-1962 -- Correspondence; Wilson, Edmund, -- 1895-1972 -- Correspondence; Oxford University Press -- Correspondence; Poets, English -- 20th century -- Biography; Classicists -- Great Britain -- Biography; Authors; Publishers